2003
DOI: 10.1097/01.asn.0000087087.61306.4a
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Transendothelial Leukocyte Migration by Iron Complexes

Abstract: Abstract. Although iron sucrose and iron gluconate are generally well tolerated in patients who are treated for renal anemia, recent clinical studies and cell culture experiments suggested significant toxicity and long-term side effects arising from the use of these iron complexes. Because of the possible role of iron in infection or cardiovascular disease, it was theorized that parenteral iron compounds influence endothelial and PMN interaction in vitro. A well-established double-chamber method was used to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 42 publications
1
36
0
1
Order By: Relevance
“…The effect of iron sucrose on blood leukocytes and endothelial cells observed previously by others in in vitro experiments [20] may also explain the reduced intraperitoneal flux of blood leukocytes.…”
Section: Discussionsupporting
confidence: 58%
“…The effect of iron sucrose on blood leukocytes and endothelial cells observed previously by others in in vitro experiments [20] may also explain the reduced intraperitoneal flux of blood leukocytes.…”
Section: Discussionsupporting
confidence: 58%
“…Both iron sucrose and ferric gluconate inhibit migration of PMNL through endothelial cells in doses equivalent to concentrations measured in the plasma of dialysis patients who were treated with these intravenous iron products. Greater impairment in PMNL migration was found when endothelial cells were incubated in vitro for iron sucrose as compared with ferric gluconate (80). Parenteral iron therapy exacerbates experimental sepsis (81).…”
Section: Critical Evaluation Of the Risk Of Iron Administrationmentioning
confidence: 99%
“…In addition, in many in vitro studies, iron has been shown to impair the immune response against pathogens. For example, incubation with iron-induced apoptosis, reduced phagocytic function and impaired transendothelial migration of polymorphonuclear leukocytes [36,37] . In keeping with these in vitro observations, iron overload resulted in the worsening of infections in various animal models in vivo [38][39][40] .…”
Section: Iron and Infection Riskmentioning
confidence: 99%